TVET educational choice of Malaysian polytechnic students - Foo, Jyy Wei; Hazri Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Students face the burden of collecting and analysing information, clarifying their own preferences, and categorizing their prioritization before making their educational choice as it is a complex and multistage process in which an individual develops aspirations to continue formal tertiary education. This paper discussed the TVET educational choice among Malaysian Polytechnics students. This study employed the QUAN-QUAL explanatory sequential design under the mixed methods model. 40 participants were purposively-selected based on their decision-making behaviour through a questionnaire (QUAN). The selected participants were divided into 10 focus groups and they were interviewed to get insights on how their educational choice was made based on their characteristics, academic credentials and decision-making behaviour (QUAL). Their responds were analysed using thematic method. Findings revealed that the main factors in the Malaysian polytechnics students’ educational choice are: 1) students’ characteristics – Academic performance in secondary school, elective subjects taken in secondary school, and field of interest 2) institutional characteristics – Courses offered by the institution, employment opportunities, financial matters, location of institution, and learning environment, 3) decision-making behaviour – Making comparison and satisficing, and 4) other related factors – Influence of others and lack of information. Understanding the students’ factors of educational choice would assist institutions in their recruitment and enrolment of students, as well as develop and implement an effective institution development plan, particularly in student recruitment management.